DINITROBENZENES STIMULATE ELECTRON FLUX WITHIN NEURONAL NITRIC OXIDE SYNTHASE IN THE ABSENCE OF CALMODULIN - Tulis, David A. (My University, 2011)
Efficient electron transfer and conversion of L-arginine to L-citrulline and nitric oxide (NO●) by neuronal nitric oxide synthase (nNOS) requires calmodulin (CaM) binding. The present study focused on electron transfer ability of resting state CaM-free nNOS in presence of dinitrobenzene isomers (DNBs). NADPH oxidation (NADPHox) and acetylated cytochrome-c reduction (AcCyt-cred) catalyzed by nNOS and the CaM binding sequencedeficient nNOS reductase construct (nNOS-FP) were estimates of total electron flux and O2● production, respectively. All the DNBs (o-, m-, p-) independently stimulated rates of NADPHox by CaM-free nNOS and by nNOS-FP in isomer- and concentration-dependent manner. Blocking nNOS heme by imidazole or L-arginine did not affect CaM-free nNOS catalyzed NADPHox stimulated by DNBs. This stimulated electron flux by DNBs did not support NO● formation by CaM-free nNOS. The DNBs, like FeCN, extract electrons from both FMN and FAD of the nNOS reductase domain. All three DNBs greatly stimulated nNOS and nNOS-FP catalyzed AcCyt-cred that was significantly inhibited by SOD demonstrating O2● formation. Thus, in presence of DNBs, resting-state CaM-deficient nNOS efficiently transfers electrons generating O2 ●, inferring that additional metabolic roles for nNOS exist that are not yet explored.
Keywords: NNOS; Superoxides; NADPH; Redox